BS EN IEC 61162-450 ED 3. Maritime navigation and radiocommunication equipment and systems. Digital interfaces. Part 450. Multiple talkers and multiple listeners. Ethernet interconnection (13th January 2022) - British Standards Institution,
No abstract available